Microcontroller based server room security system with dual authentication and Telegram as access data - Medifa, Ibra; Elvanny Myori, Dwiprima (Journal of Industrial Automation and Electrical Engineering, 2025)
Server space security is a critical aspect that requires a robust protection system. Traditional single-authentication security systems have weaknesses against access theft and lack real-time monitoring features. This research aims to design an ESP32-based server room security system with dual authentication using RFID and PIN, as well as monitoring via Telegram. The system integrates ESP32 as the main microcontroller, RFID MFRC522, TFT LCD touchscreen, ESP32-CAM, solenoid lock door, buzzer, and push button with Telegram API for real-time notifications. The research methodology includes hardware design and software development using the Arduino IDE. The test results showed that the system successfully implemented dual authentication with a 100% success rate for valid access, was able to deny access with an incorrect PIN or unregistered card, and successfully sent notifications and images to Telegram in real-time. The system provides significant improvements to server space security through multi-layered authentication, remote monitoring, and comprehensive access documentation.